2021
DOI: 10.1002/aoc.6188
|View full text |Cite
|
Sign up to set email alerts
|

Structure controlled Au@Pd NPs/rGO as robust heterogeneous catalyst for Suzuki coupling in biowaste‐derived water extract of pomegranate ash

Abstract: This article explores the aptness of water extract of pomegranate ash (WEPA) of agro‐waste origin as an effective media for a heterogeneous reduced graphene oxide (rGO)‐supported Au–Pd bimetallic nanoparticles (NPs)‐catalyzed Suzuki coupling without the need of additional ligand, base, and additives at room temperature. Morphological and structural details of Au–Pd bimetallic nanoparticles/rGO are evaluated using a suite of electron microscopy, X‐ray diffraction, and cyclic voltammetry techniques. A facile che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…In the same year, Ramamoorthy et al developed Au core -Pd shell / rGO as a catalyst for Suzuki coupling reaction in pomegranate ash as an additive and in presence of ethanol as solvent at room temperature under open air (Scheme 30). [91] They investigated broad scope extension with a high yield obtained. Furthermore, the hydrogen adsorption region was monitored from CV (cyclic voltammetry) as a prepared catalyst (fresh and used), and no changes were observed in that surface area.…”
Section: In Suzuki Coupling Reactionmentioning
confidence: 99%
“…In the same year, Ramamoorthy et al developed Au core -Pd shell / rGO as a catalyst for Suzuki coupling reaction in pomegranate ash as an additive and in presence of ethanol as solvent at room temperature under open air (Scheme 30). [91] They investigated broad scope extension with a high yield obtained. Furthermore, the hydrogen adsorption region was monitored from CV (cyclic voltammetry) as a prepared catalyst (fresh and used), and no changes were observed in that surface area.…”
Section: In Suzuki Coupling Reactionmentioning
confidence: 99%
“…The analysis shows 0.98 ppm of Pd leaching after the first catalytic cycle. It was found that the mechanism of Pd-nanoparticle-catalyzed C–C coupling reactions can be homogeneous, heterogeneous, or a mixture of those two mechanisms (oxidative addition at Pd NP surface, followed by the leaching of the [Pd­(Ar)­X] species, which goes through the homogeneous catalytic cycle). The loss of catalytic activity in the recyclability test of the Suzuki–Miyaura cross-coupling reaction could be the result of the homogeneous or mixed (homogeneous–heterogeneous) reaction mechanism. Thus, the result of the recyclability test implies that the redeposition of homogeneous palladium species on the CVS-ZnO support is not efficient enough.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of Au-Cu/NPZ/CPE was done via Galvanic replacement technique and the sensor represented favorable analytical properties such as rapid response time, high sensitivity and wide linear range. Graphene oxide supported Au-Pd bimetallic nanoparticle with a core-shell morphology was synthesized by using water extract of pomegranate ash (WEPA) [32]. The core-shell structure of Au-Pd/rGO made a positive contribution in achieving the Suzuki coupling reaction in a very short time.…”
Section: Bio-waste Approach For Synthesizing Bimetallic Nanoparticlesmentioning
confidence: 99%